Determining Service Needs for xxx Students in Batam Using Work Sampling - Albertus Laurensius Setyabudhi (YCMM, 2022)
The goal from this research is knowing number of needs worker in the service for student. There is three objective in this research. The research use work sampling with time study. Research input is all of service activites for student. With observe and make pie chart diagram we make a conclusion. The conclusion is service for student has a good job, they have 74% productive activities. The most activites is servicing the student and we don’t need additional worker. But we need to know standart time for the service next time and may be this research can be use for another case in the university.